Strategic Linkages for Innovation in the Biotechnology Industry in Malaysia - Azhar, Adlan Hafiz (2013)
National Innovation Systems is a framework developed to measure the economic contributions of innovation which cannot be captured by mainstream macroeconomic theory. The National Innovation System looks at the interactions between the Public sector, the private sector and all stakeholders which creates, develops and markets the technologies. In terms of the industry in question for this research, the Biotechnology industry was chosen as it relies closely on innovation and high capital Research and Development, and as such is highly relevant for the study on National Innovation System A background literature exercise was conducted which had highlighted the key themes or parameters which can be used to gauge the success of the NIS level in the Biotechnology industry in Malaysia. From there, a review of the official policy documents as well as other publications on the Biotechnology industry in Malaysia was conducted and a questionnaire was developed to gauge and understand the industry from the players on the ground. Based on the review of the reports and the respondent’s questionnaires, several conclusions were derived. Firstly, the biotechnology industry is one that is strongly supported by the government; however, there are several implementation issues that are present. Secondly, the need for talented human capital and alternative funding sources is present due to the nature of the Biotechnology industry, despite the conducive economic conditions. Finally, the interactions between the stakeholders need to be increased to ensure a strong National Innovation System for the industry which will provide sustained growth and development of the Biotech industry in Malaysia.